A escola por trás das grades : educação escolar no sistema prisional do Estado do Paraná, 1990-2016 - Rocha, Fabiana Virginio da (2016)
This study is characterized as qualitative, exploratory and field focusing on the reality of the State Penitentiary in Maringa, Parana, and has as theoretical framework Sergio Adorno (1991), Michel Foucault (2013), Marc Mayer (2006) to discuss public education policies for the prison system in Parana State, from 1990 to 2016. The goal of this study is to understand about this policies setup and the social function of youth and adults education (EJA program) in deprivation of liberty in prisons; by checking the emergence of dialogue between public policy education and public security policy, discussing the documents that guarantee the legality of the provision of prison education in Brazil and in the state of Parana; presenting data about prisons, prison population and the provision of education for prisoners, emphasizing the State Penitentiary Maringa (PEM). The work shows the difficulties in developing, effectively, an education program in a field characterized by the existence of contradictions and also reflects on the impact of these policies for the whole society. The study also highlights that unlike other areas in which EJA was implemented, the prison needs to be re-signified as potentially educational space, since the prisons were designed in with the objective of serving as an instrument of punishment and not schooling